Highland treasure ebook - Sands, Lynsay (Highland Brides, 2021)
A Buchanan brother finds a love to treasure in this scintillating historical romance from New York Times bestselling author Lynsay Sands... After escaping from the English soldiers who attacked her home and imprisoned her in a dungeon, Lady Elysande de Valance is grateful for the rugged Scots who are escorting her to safety in the Highlands. Even with danger dogging their every step, she hadn't expected to welcome the strong comforting embrace of their leader, Rory Buchanan. They say he's a healer, but she finds the heat of his touch does so much more... Let his brothers get married—Rory is too busy tending to the sick to be bothered with wooing a bride. But when he is tasked with accompanying a family friend's "treasure" to the Highlands, he is surprised to learn the treasure is a beautiful woman on the run—and even more surprised to discover bruises hidden by her veil. Rory makes it his mission to tend to her injuries and protect her, but the thought of losing her makes him realize that perhaps it is his heart that is most in need of healing...